Penggunaan Media Teknologi Chromebook pada Pembelajaran Pendidikan Pancasila dalam Meningkatkan Minat Belajar Siswa (Lembaga Pengembangan Kinerja Dosen, 2026)
This study analyzes the application of Chromebook technology and its impact on increasing the learning interest of seventh-grade students in Pancasila Education at UPTD SMP Negeri 6 Gunungsitoli. The background of the problem shows low student interest in learning due to conventional lecture methods, even though Pancasila Education is essential for character building. Chromebooks are identified as an innovative solution for interactive learning. This two-cycle qualitative classroom action research (PTK) involved 20 students, using observation, learning interest questionnaires, and learning outcome tests as data collection instruments. The results showed that the implementation of Chromebooks successfully improved teachers' (91.63%) and students' (90.15%) abilities to the “very good” category. Student learning interest increased significantly (93.83%, “very good” category), followed by improved learning outcomes (average 91.19% with 100% of students meeting the minimum competency standard). It was concluded that the use of Chromebooks effectively enhances student interest and learning outcomes, creating an active and interactive learning environment. Recommendations include school support, enhancing teachers' digital competencies, and active student participation in technology-based learning